2017
DOI: 10.1136/heartjnl-2016-310610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cost sharing on adherence to evidence-based medications in patients with acute coronary syndrome

Abstract: ObjectivesCost-sharing scheme for pharmaceuticals in Spain changed in July 2012. Our aim was to assess the impact of this change on adherence to essential medication in patients with acute coronary syndrome (ACS) in the region of Valencia.MethodsPopulation-based retrospective cohort of 10 563 patients discharged alive after an ACS in 2009–2011. We examined a control group (low-income working population) that did not change their coinsurance status, and two intervention groups: pensioners who moved from full co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
5
28
1
3
Order By: Relevance
“…Another study, which linked prescription and dispensing information, assessed the impact of the coinsurance rate on non-adherence to acute coronary syndrome drugs. In line with our results, the study showed an increase in non-adherence to costly drugs and this was especially pronounced in the pensioner population 12. IMNA occurs when a first prescription of a new treatment is not dispensed, and rational use of medicines is not relevant, although it could partially explain IMNA in analgesics 16.…”
Section: Discussionsupporting
confidence: 88%
“…Another study, which linked prescription and dispensing information, assessed the impact of the coinsurance rate on non-adherence to acute coronary syndrome drugs. In line with our results, the study showed an increase in non-adherence to costly drugs and this was especially pronounced in the pensioner population 12. IMNA occurs when a first prescription of a new treatment is not dispensed, and rational use of medicines is not relevant, although it could partially explain IMNA in analgesics 16.…”
Section: Discussionsupporting
confidence: 88%
“…As medication non-adherence has been associated with worse outcomes and higher costs,3 it has become an area of particular interest to policy-makers. The article by Gonzalez et al , published in Heart ,4 attempts to examine this timely and important topic.…”
mentioning
confidence: 99%
“…Greater use of medical services and productivity losses are also consequences of from medication non-adherence, which places a signi cant cost burden on healthcare systems [8,9]. Non-adherence is higher when more expensive medicines are prescribed and when co-payment is applied [4,10,11]; interventions that reduce the co-payment contributions or exempt the patient from payment have effectively proven to reduce nonadherence [12,13].…”
Section: Introductionmentioning
confidence: 99%